2008
DOI: 10.1007/s11046-008-9095-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Antibodies to Paracoccidioides brasiliensis in Dairy Cattle from Mato Grosso do Sul, Brazil

Abstract: The aim of this study was to evaluate the humoral immune response in cattle immunized with Paracoccidioides brasiliensis and perform a seroepidemiological study of paracoccidioidomycosis in dairy cattle from Mato Grosso do Sul. Two animals (one steer and one heifer) were inoculated with a suspension of P. brasiliensis in Freund incomplete adjuvant. Blood samples were collected periodically to evaluate humoral immune response by immunodiffusion and ELISA, using exoantigen and gp43 as antigens, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Epidemiological studies of PCM in domestic and wild animals have been based mainly on immunological reactions using crude paracoccidioidin and purified gp43 as antigens [5][6][7][8][9][10][11][12][13][14][15][16]32]. Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies of PCM in domestic and wild animals have been based mainly on immunological reactions using crude paracoccidioidin and purified gp43 as antigens [5][6][7][8][9][10][11][12][13][14][15][16]32]. Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…presence in endemic areas. Infection by P. brasiliensis has been reported in domestic and wild animals such as dogs [5][6][7], horses in Uruguay and in Brazil [8,9], cows in Colombia and Brazil [10,11], sheep, goats and chickens in Brazil [12][13][14], and monkeys [15] and armadillos in Brazil [16]. P. brasiliensis isolates were obtained from soil samples in Argentina [17], Venezuela [18] and Brazil [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente esta técnica passou a ser utilizada também em estudos epidemiológicos de paracoccidioidomicose em humanos (BOTTEON et al, 2002), cães (ONO et al, 2001;SILVEIRA et al, 2006), macacos (CORTE et al, 2007) e bovinos (SILVEIRA et al, 2008).…”
Section: Resultsunclassified
“…A infecção por P. brasiliensis tem sido demonstrada em diferentes espécies de animais domésticos como cães, bovinos, eqüinos e silvestres como macacos e felinos (CORTE et al, 2007;MÓS;FAVA NETTO, 1974;ONO et al, 2001;SILVEIRA et al, 2006SILVEIRA et al, , 2008. Considerando a escassez de dados sobre a ecoepidemiologia da paracoccidioidomicose, este estudo teve como objetivo avaliar a infecção por P. brasiliensis em cavalos da Região Norte do Estado do Paraná.…”
Section: Introductionunclassified
“…Epidemiological studies have shown that paracoccidioidomycosis occurs in several species of domestic and wild animals such as dogs (Mós & Fava-Netto 1974, Ono et al 2001, Silveira et al 2006, Canteros et al 2010, Fontana et al 2010, cows (Silveira et al 2008), horses (Conti Diaz et al 1972, Costa & Fava-Netto 1978, Corte et al 2009), armadillos (Fernandes et al 2004), sheep (Costa & Fava-Netto 1978, Oliveira et al 2011, monkeys (Corte et al 2007), guinea pigs, raccoons, grisons, porcupine (Richini-Pereira et al 2008) and chickens (Gonçalves et al 2011). The fungus was also isolated from armadillos (Naiff et al 1986, Bagagli et al 1998, Corredor et al 1999, Silva-Vergara et al 2000 penguin faeces (Gezuele 1989), and recently, natural paracoccidioidomycosis was reported in two dogs (Ricci et al 2004, Farias et al 2011), a cat (Gonzalez et al 2010) and a two-toed sloth (Trejo-Chávez et al 2010).…”
Section: Introductionmentioning
confidence: 99%